Geometric morphometric analysis of the bony labyrinth of the Sima de los Huesos hominins. Issue 174 (January 2023) - Velez, Alex D.; Quam, Rolf; Conde-Valverde, Mercedes; Martínez, Ignacio; Lorenzo, Carlos; Arsuaga, Juan Luis
Abstract: The bony labyrinth contains phylogenetic information that can be used to determine interspecific differences between fossil hominins. The present study conducted a comparative 3D geometric morphometric analysis on the bony labyrinth of the Middle Pleistocene Sima de los Huesos (SH) hominins. The findings of this study corroborate previous multivariate analyses of the SH hominin bony labyrinth. The analysis of the semicircular canals revealed the SH hominin canal morphologies appear closer to those of the Neandertals than to those of Homo sapiens . This is attributable to a Neandertal-like ovoid anterior canal, and mediolaterally expanded, circular posterior canal. However, the SH hominins lack the increased torsion in the anterior canal and the inferior orientation of the lateral canal seen in Neandertals. The results of the cochlear analysis indicated that, although there is some overlap, there are notable differences between the SH hominins and the Neandertals. In particular, the SH hominin cochlea appears more constricted than in Neandertals in the first and second turns. A principal component analysis of the full bony labyrinth separated most SH hominins from the Neandertals, which largely clustered with modern humans. A covariance ratio analysis found a significant degree of modularity within the bony labyrinth of all three groups, with the SH hominins and Neandertals displaying the highest modularity. This modular signal in the bony labyrinth may be attributable to different selective pressures related to locomotion and audition. Overall, the results of this study confirm previous suggestions that the semicircular canals in the SH hominins are somewhat derived toward Neandertals, while their cochlea is largely primitive within the genus Homo .